2022
DOI: 10.1007/s10648-022-09695-0
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs About Inclusive Education and Insights on What Contributes to Those Beliefs: a Meta-analytical Study

Abstract: Teachers’ belief systems about the inclusion of students with special needs may explain gaps between policy and practice. We investigated three inter-related aspects of teachers’ belief systems: teachers’ cognitive appraisals (e.g., attitudes), emotional appraisal (e.g., feelings), and self-efficacy (e.g., agency to teach inclusive classrooms). To date, research in this field has produced contradictory findings, resulting in a sparse understanding of why teachers differ in their belief systems about inclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 215 publications
6
36
0
1
Order By: Relevance
“…This finding could suggest that trainee teachers, who have actual experience with teaching, exhibit reduced self-efficacy expectations with respect to certain teaching constellations and specific pupils. This finding is in line with the results of a recent meta-analysis (Dignath et al, 2022), which reports that "self-efficacy beliefs were found to be higher for preservice than for in-service teachers" (p. 24). Other scholars likewise emphasize the effect of teaching experience on attitudes toward inclusive education (e.g., Avramidis and Kalyva, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding could suggest that trainee teachers, who have actual experience with teaching, exhibit reduced self-efficacy expectations with respect to certain teaching constellations and specific pupils. This finding is in line with the results of a recent meta-analysis (Dignath et al, 2022), which reports that "self-efficacy beliefs were found to be higher for preservice than for in-service teachers" (p. 24). Other scholars likewise emphasize the effect of teaching experience on attitudes toward inclusive education (e.g., Avramidis and Kalyva, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…This approach builds on Bandura’s (1977) concept of self-efficacy , which is defined as a belief in one’s competence to achieve goals in a certain situation. For instance, teachers’ self-efficacy has been repeatedly linked to teaching outcomes ( Klassen and Chiu, 2010 ) as well as their beliefs and attitudes ( Dignath et al, 2022 ) in inclusive educational settings. Therefore, it can be presumed that descriptions of biogenetic causes can help reduce stigmatization, for example, because they lead to the belief that the affected person is not to blame for his or her condition.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason we have such a finding might be because the comparison group was already enrolled in "Inclusive Education" course which might also influence their sensitivity and raise their awareness about key issues related to interventions. Similarly, in a recent meta-analysis, the researchers reported that inclusive education training can change teachers' professional beliefs and experience (Dignath et al 2022). However, the findings of our study showed that a 14-week training did not have as strong impact on the emotion regulation strategies as we expected, because these strategies are mostly shaped by individual experiences and mutual relationships from early ages.…”
Section: Discussionmentioning
confidence: 93%
“…Speci cally, teachers' knowledge, skills and beliefs, as well as students' academic achievement, learning behavior, and attitudes toward school, are commonly assessed. Reviews report positive in uences of professional development participation but include only a few primary studies in their analyses, with considerable variations in reported effect sizes (Avramidis & Norwich, 2002;Brock & Carter, 2017;Dignath et al, 2022). However, these studies focus on speci c aspects of diversity (i.e., special educational needs) or isolated outcome measures (e.g., attitude; Dignath et al, 2022, or implementation delity; Brock & Carter, 2017).…”
Section: Previous Reviewsmentioning
confidence: 99%
“…The current study aims to identify aspects that enhance the effectiveness of professional development in addressing inclusive education. In order to extend the range of information gathered, we do not limit geographical areas and include studies with different designs in this meta-analysis (Dignath et al, 2022;Katsarov et al, 2022). The inclusion of different study designs has been discussed in the literature (Mueller et al, 2018) and this practice has become more common practice, as it can help answer the question of underlying effects and analyze biases introduced by the different designs (Price et al, 2004).…”
Section: Study Aimsmentioning
confidence: 99%